Pengenalan Angka Pada Anak Sekolah Dasar Berbasis Macromedia Flash - Ali Ikhwan; Fauziatun Husna; Sinta Dara Efita; Randa Syuhada; Gilang Ramadhan (Jurnal Sains dan Teknologi (JSIT), 2023)
Based on the results of observations on students at SDN 101827 Tuntungan there were still students whose knowledge of numbers was lacking. This is evident from the low reading ability of students in one class, there were 18 students and half of the 18 people were fluent in counting while the rest were still not fluent in counting and knowing numbers, could not count correctly and some even did not know numbers perfectly. Overcoming these problems requires learning media that are new and interesting and can attract students to read, one of which is macromedia flash-based learning. This study aims to plan interactive Macromedia flash media so that students can improve their numeracy skills. The method used is the Reseach and Development stage in this research beginning with potentials and problems, data collection, product design, design validation, design revision and usage testing. The results showed that the developed media met the requirements and eligibility to be used as learning media. And the results of the product use test, namely: the results of the assessment of the learning aspects of 75% in the good category and the results of the assessment of the aspect of purchasing materials 80% in the very decent category the results of the assessment of learning aspects obtained an average score of 80% in the very good category.